Responses of peatland vegetation to 15-year water level drawdown as mediated by fertility level - Kokkonen, Nicola A K; Laine, Anna Maria; Laine, Jukka; Vasander, Harri; Kurki, Kirsi; Gong, Jinnan; Tuittila, Eeva-Stiina (Supplement to: Kokkonen, NAK et al. (2019): Responses of peatland vegetation to 15-year water level drawdown as mediated by fertility level. Journal of Vegetation Science, 30(6), 1206-1216, https://doi.org/10.1111/jvs.12794, 2019)
Peatland vegetation community data following experimental water level manipulation with measurements repeated six times in 15 years.
Keywords: community; Peatland; repeated measurements; sphagnum; Vegetation; water level drawdown